2013
DOI: 10.1111/bcpt.12062
|View full text |Cite
|
Sign up to set email alerts
|

Medication Reviews by Clinical Pharmacists at Hospitals Lead to Improved Patient Outcomes: A Systematic Review

Abstract: Suboptimal medication use may lead to morbidity, mortality and increased costs. To reduce unnecessary patient harm, medicines management including medication reviews can be provided by clinical pharmacists. Some recent studies have indicated a positive effect of this service, but the quality and outcomes vary among studies. Hence, there is a need for compiling the evidence within this area. The aim of this systematic MiniReview was to identify, assess and summarize the literature investigating the effect of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
158
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(175 citation statements)
references
References 136 publications
(167 reference statements)
15
158
1
1
Order By: Relevance
“…Medication reviews by clinical pharmacists have provided promising results among hospitalised patients, with one study for example showing a reduced rate of readmissions, prolonged time to readmissions and a reduction in the length of the hospital stay [23]. There are other examples that have shown reduced rates of drug-related readmissions after the introduction of medication reviews [22,24], and yet, another review showed that medication reviews performed by clinical pharmacists led to improved patient outcomes, such as improved quality of prescribing and reduced costs [40]. There is still a need for more studies, and in particular randomised controlled trials, to evaluate the effects of medication reviews in different patient groups, but it should also not be forgotten that the implementation of medication reviews might have positive indirect effects.…”
Section: Discussionmentioning
confidence: 99%
“…Medication reviews by clinical pharmacists have provided promising results among hospitalised patients, with one study for example showing a reduced rate of readmissions, prolonged time to readmissions and a reduction in the length of the hospital stay [23]. There are other examples that have shown reduced rates of drug-related readmissions after the introduction of medication reviews [22,24], and yet, another review showed that medication reviews performed by clinical pharmacists led to improved patient outcomes, such as improved quality of prescribing and reduced costs [40]. There is still a need for more studies, and in particular randomised controlled trials, to evaluate the effects of medication reviews in different patient groups, but it should also not be forgotten that the implementation of medication reviews might have positive indirect effects.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists’ interventions (PIs) are generally highly accepted 28. Graabæk and Kjeldsen28 systematically reviewed the impact of pharmacists’ medication reviews in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Graabæk and Kjeldsen28 systematically reviewed the impact of pharmacists’ medication reviews in hospitals. High acceptance rates (>69%) were reported in 16 out of the 31 included publications (ranging from 39% to 100%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds well with the high acceptance rate (84%) and demonstrates high clinical relevance of the pharmacist’s input. Other clinical studies have reported acceptance rates varying from 39% to 100%,11 which supports the importance of clinical pharmacist’s contribution to ensure rational pharmacotherapy. It would have strengthened our results if evaluation from physicians in primary care also had been included, but this was due to practical circumstances not possible.…”
Section: Discussionmentioning
confidence: 83%